UNDERSTANDING STUDENT’S WORK READINESS: INDIVIDUAL-SOCIAL PERSPECTIVES - Fatia Nurul Salma (Journal of Research in Organizational Behaviour, 2023)
This research has the aim of examining the analysis of the influence of competence and social support on work readiness on student’s work readiness in final students with self-efficacy as a moderating variable. The total population was 658 people and took a sample of 132 people using the proportionate stratified method. This type of research is quantitative research with SEM PLS analysis technique. Based on the results of these findings, it is found that competence has significantly and positively impact on work readiness. Social support has no impact on work readiness. Self-efficacy moderates the impact of competence on work readiness and self-efficacy. Self-efficacy does not moderate social support on work readiness.